ANALISIS KEPUTUSAN PEMBELIAN PAKET WISATA ALAM OLEH USER MEDIA SOSIAL INSTAGRAM - Purba, Indra Setiawan; Ariwibowo, Prasetio (Fakultas Ekonomi Universitas Darul 'Ulum Jombang, 2018)
The method used in this research is descriptive analysis method, regression analysis, and hypothesis testing with simple linier regression analysis and coefficient of determination analysis. In this study, the population is a student of Jakarta Capital City who has social media instagram and has never bought natural tourism package. The validity test used in this research is using Convirmatory factor analysis (CFA) technique. The low validity of a questionnaire instrument can be measured by loading factor with SPSS 20.00 for Windows. Based on the results of simple regression calculation obtained a = 98.145 and b = 0.27 form regression Y = 98.145 + 0.27X. Interpretation of the regression equation model is any change of X variable scores for one unit, then the variable Y increases by 0.27 in the same direction with the constant 98.14 Provided Coefficient of Determination (KD) of 0.0225, this shows that the contribution of attitude on social media instagram (X ) to the decision of purchasing natural tourism package (Y) is equal to 2,25% and contribution by other factor equal to 97.75%. Based on t arithmetic <t table (1.485 <1.984), it means there is very low influence between attitude on social media instagram to decision of purchasing nature tour package.